DETERMINANTS OF ONLINE SHOPPING BEHAVIOR CASE STUDY: STUDENTS OF FACULTY OF ECONOMIC AND BUSINESS, IBA UNSRAT - Sukisman, Menthari R.; Tumbuan, Willem J. F. A.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The main takeaways of online shopping platforms now are it created layers of opportunity and ways of purchasing for the people; however, the problem rises regarding the approach of online shopping behavior itself. With the condition of university students regarding their young age; this type of people is really prone regarding the existence of online shopping. The purpose of this study is to find out the determinants of online shopping behavior of Shoppe users as part of E-Commerce, particularly the users are students of IBA Unsrat. This study uses a qualitative method and interview toward informants were conducted in order to gain information regarding the phenomenon. The findings of this study shows that online shopping behavior which constructed by 5 indicators of brand loyalty, visual merchandising, decision factors, product attributes and also discount can give effect toward the userâ€™s behavior in doing online shopping behavior. Based on the result, the researcher provided several recommendations which are: for the consumers; considerations regarding the level of importance in using online shopping behavior. For the company; the utilization on large scale and improvement of the online shopping platform needs to be done in order to gain more users. Â Keywords: online shopping behavior, e-commerce